Capacity Building from the Inside Out: Development and Evaluation of a CITI Ethics Certification Training Module for American Indian and Alaska Native Community Researchers - Pearson, Cynthia R.; Parker, Myra; Fisher, Celia B.; Moreno, Claudia (Journal of empirical research on human research ethics, 2014)
Current human subject research training modules fail to capture ethically relevant cultural aspects of research involving American Indian and Alaska Native (AI/AN) community members. Applying a Community Engaged Research (CEnR) approach, we adapted the Collaborative IRB Training Initiative training module “assessing risk and benefits.” In a two-arm randomized controlled trial, followed by debriefing interviews, we evaluated module acceptability and understandability (test scores) among 40 reservation-based community members. Participants who took the adapted module, compared to those who took the standard module, reported higher scores on relevance of the material overall satisfaction, module quiz scores, and a trend toward higher self-efficacy. Implications of the efficacy of this approach for enhancing ethics training and community participation in research within AI/AN and other cultural populations within and outside the United States are discussed.